Diagnosis of the Travel and Tourism Competitiveness Index Methodology on the Example of Poland’s Position on the Tourist Market - Małgorzata Januszewska; Daria Jaremen; Elżbieta Nawrocka (Barometr Regionalny, 2018)
The purpose of the article is to assess Poland’s position on the international tourist market taking a comparative approach, in the light of the Travel and Tourism Competitiveness Index (TTCI) developed by the World Economic Forum (WEF), and also critical analysis of the TTCI methodology used in the years 2009–2016. The countries (Czech Republic, Slovak Republic, Hungary, Lithuania, Latvia and Estonia) indicated by the Polish Tourism Organization as the most important competitors were selected for the comparative analysis of Poland’s position on the tourist market. The research proved that in the analyzed period the position of Polish tourism against the background of competitors is growing as a result of the significant improvement of the Travel & Tourism regulatory framework and infrastructure. The WEF methodology is not yet perfect due to the selection and number of respondents, whereas the modification of competition factors, consistent with the evolution of theoretical concepts and also keeping up with the progress in business practice, deserves a positive assessment.